JUGULAR FORAMEN SCHWANNOMA-A VERY RARE ENTITY - Ahmad, Manzoor; Butt, Rizwan Masood; Ahmad, Nazir (Journal of Ayub Medical College Abbottabad, 2009)
Jugular foramen schwannoma is a very rare tumour and very few cases have been reported in the literature. Usually it is misdiagnosed as acoustic neuroma and the diagnosis is made peroperatively. It has significant neurological morbidity and mortality. In addition to the experience and expertise of the surgeon, introduction of better anaesthesia and microsurgical techniques have significantly reduced the morbidity and mortality. We present a case of jugular foramen schwannoma who was operated by the senior author. The outcome was very good and the patient recovered without any permanent deficits. The epidemiology, pathophysiology, clinical features, radiographic findings and treatment of this rare entity are reviewed. Keywords: Jugular foramen, schwannoma, surgical options, outcome